Evaluation of Surface Humidification of Exterior Insulation and Finish Systems - Eva Barreira (2016)
Exterior insulation and finish systems (EIFSs) are common in Europe nowadays. These systems bring thermal benefits, in addition to being cheap and easy to apply, but there are often serious problems with biological growth, causing cladding defacement. The physical phenomenon causing EIFS defacement is known, and mathematical models simulating its performance have been developed. However, no simple process exists to evaluate the risk of EIFS surface humidification (which contributes to surface defacement) that might be used by designers and by the building industry. This paper presents a methodology to assess EIFS surface humidification based on the definition of indices that combine the effect of surface condensation, wind-driven rain, and the drying process, three of the most prevalent parameters influencing surface moisture content. The proposed indices were calculated using data collected during a 1-year in situ test campaign, which provided information about the exterior climate conditions and the surface temperature and wind-driven rain on four EIFS-covered facades facing the cardinal directions. The indices were compared with the results of the surface moisture measured simultaneously, which allowed the methodology to be validated. This paper also presents an example of the practical use of this methodology using a definition of hazard classes of surface humidification of EIFS-covered facades located in Portuguese territory.